Modeling dynamic systems: contribution to the unsteady behavior of a condenser based on the pseudo-bond graph approach. (2nd January 2020) - Kebdani, M.; Dauphin-Tanguy, G.; Dazin, A.
ABSTRACT: This article is devoted to the dynamic study of the brazed plate condenser (BPC). The proposed model is based on the bond graph theory. The proposed model is based on the bond graph theory because of its energetic approach and multi-physics character of the studied system. The model is discretized into five control volumes. The resolution of mass and energy equations is done by Runge-Kutta method embedded in 20sim software. Analyses of simulation results show that the model has a good ability to transcribe the time evolution of the temperature and pressure in both regimes, transitional and permanent. Also, the model is experimentally validated without any fitting of the set of thermal exchange coefficients.